Risk of Brain Metastases in Patients with Non-metastatic Lung Cancer: Analysis of the Metropolitan Detroit Surveillance, Epidemiology, and End Results (SEER) Data - Goncalves, Priscila H. (Cancer, 2016)
BACKGROUND: Brain metastases (BM) remain an important cause of morbidity and mortality in lung cancer patients. Our study evaluated population-based incidence and outcomes of BM in patients with non-metastatic lung cancer. METHODS: Patients diagnosed with non-metastatic first primary lung cancer, between 1973–2011, in the Metropolitan Detroit Surveillance Epidemiology and End Results (SEER) registry were used for analysis. Age-adjusted Odds Ratios (OR) of developing BM based on various demographic characteristics and histology were calculated with 95% confidence intervals (CIs). Adjusted Cox Proportional Hazards Ratios and Log Rank Tests of Kaplan-Meier Survival Curves were calculated to evaluate survival differences for non-small cell (NSCLC) and small cell lung cancers (SCLC). RESULTS: The incidence of BM in non-metastatic NSCLC and SCLC was 9% and 18% respectively. There was variation in the incidence of BM according to NCSLC histology. Incidence of BM was higher in patients < 60 years old in both NSCLC and SCLC, but there were no differences by race for either histological group. Female patients with NSCLC were more likely to have BM than males. There was variation in proportion of BM in both NSCLC and SCLC patients over the three 13-year of diagnosis periods. Risk of death (hazard ratio, HR) was significantly higher for those with BM in NSCLCs, but not significantly higher in SCLC. CONCLUSIONS: The incidence of BM in non-metastatic lung cancer patients varies according to histology, age, and sex. BM are associated with worse survival for NSCLC but not SCLC.